2015
DOI: 10.1104/pp.114.252908
|View full text |Cite
|
Sign up to set email alerts
|

An R2R3-MYB Transcription Factor Regulates Eugenol Production in Ripe Strawberry Fruit Receptacles

Abstract: Eugenol is a volatile phenylpropanoid that contributes to flower and ripe fruit scent. In ripe strawberry (Fragaria 3 ananassa) fruit receptacles, eugenol is biosynthesized by eugenol synthase (FaEGS2). However, the transcriptional regulation of this process is still unknown. We have identified and functionally characterized an R2R3 MYB transcription factor (EMISSION OF BENZENOID II [FaEOBII]) that seems to be the orthologous gene of PhEOBII from Petunia hybrida, which contributes to the regulation of eugenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 78 publications
(139 reference statements)
8
88
1
Order By: Relevance
“…RT-qPCR amplification was performed under the following conditions: 40 cycles at 95°C for 30 s and 58°C for 30 s. After amplification, the samples were maintained at 50°C for 1 min, and the temperature was gradually increased by 0.5°C every 10 s to perform the melting curve analysis. The interspacer 26S-18S strawberry RNA gene (housekeeping gene; Fv18S ) was used as an internal control to normalize the expression data (Raab et al, 2006; Hu et al, 2015; Medina-Puche et al, 2015; Paniagua et al, 2016; Wei et al, 2016). Three biological replicates with three technical replicates were assayed for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR amplification was performed under the following conditions: 40 cycles at 95°C for 30 s and 58°C for 30 s. After amplification, the samples were maintained at 50°C for 1 min, and the temperature was gradually increased by 0.5°C every 10 s to perform the melting curve analysis. The interspacer 26S-18S strawberry RNA gene (housekeeping gene; Fv18S ) was used as an internal control to normalize the expression data (Raab et al, 2006; Hu et al, 2015; Medina-Puche et al, 2015; Paniagua et al, 2016; Wei et al, 2016). Three biological replicates with three technical replicates were assayed for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…It has been extensively shown that MYB TFs activate or repress genes associated with pigment/anthocyanin production of fruits (An et al ., ; Xu et al ., ; Yao et al ., ). In addition, several MYB TFs like FaMYB10 and FaEOBII, mediate the production of volatile compounds by targeting phenylpropanoid pathway genes during strawberry fruit ripening (Medina‐Puche et al ., , ). Similarly, in apple MdMYB1/10/73 modulate fruit organic acid accumulation by directly activating vacuolar transporters (Hu et al ., ,b, ).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation analysis of the transcriptomes of ripening fruits also identified three TFs of the MYB, TCP and SCL families that were positively correlated with flavonoid accumulation in ripening fruits (Pillet et al , ). Recently, other TFs have been reported to regulate the gene expression of eugenol synthase2 (Medina‐Puche et al , ; Molina‐Hidalgo et al , ), which is involved in the synthesis of eugenol (Aragüez et al , ).…”
Section: Introductionmentioning
confidence: 99%